THE ROLE OF GAMES IN AUDIOVISUAL ART EDUCATION - Коваленко, Юлія; Логінова, Тетяна (SWorldJournal, 2023)
The study examines game-based learning methods used in the teaching of professional disciplines at audiovisual faculties. The functional differences and introduction of game technologies at all levels of education – from practical courses, school educati